The Students' Perception On Characteristics Of English Lecturer At Universitas Muhammadiyah Surakarta - Buanawati, Ilhama (2017)
Abstract This study aims at investigating the students' perception on the characteristics of English lecturer. It focuses on: the students' perceptions about English lecturer's characteristics of English department in University Muhammadiyah of Surakarta. This research was done by interviewing three students of English Department of UMS. The object of the study was the characteristics of English lecturer. The data came from students' perception, in the form of interview transcript. This research found three themes, they are: (1) a good character (2) bad character (3) expected character. Keywords: students' perception, lecturer characteristics, English lecturer